(untitled) (Bangladesh Journal of Animal Science, 2026)
Heat stress has serious physiological and economic consequences in dairy farming. It occurs when ambient temperature exceeds thermoneutral zone, typically above 24°C along with high humidity. Crossbred dairy cows are vulnerable to heat stress due to their low adaptation capacity and higher metabolic heat production. Heat stress results a marked decline in milk production (10-25%), milk fat and protein level as well as reduced reproductive performances. Additionally, heat stress leads to significant economic losses arising from decreases feed intake (up to 40%), increases water intake (up to 200 liters), greater culling frequency & increases farmer liability with veterinary expenses. Some potential interventions have stated to be effective in limiting the adverse effects of heat stress e.g., appropriate housing fitted with optimum ventilation and right amount of shade covers. Others include cooling systems like fans and sprinklers as well as proper nutritional management. Moreover, high-energy diets, electrolyte and antioxidant supplementation, and addition of rumen-protected nutrients, and long-term genetic selection of heat-tolerant animals are also an option. Cost-effective and integrated heat stress mitigations focused on prompt management interventions, are necessary to alleviate heat stress and make dairy production sustainable. Bangladesh Journal of Animal Science 55 (1): 21 - 45, 2026